Repurchase Intention Dipengaruhi Green Marketing Dan e-WOM Melalui Brand Image Kopi Kekinian di Kota Kediri - Yani, Ahmad; Evasari, Aprilia Dian (Universitas Islam Kadiri, 2024)
This study aims to identify and analyze the influence of green marketing and e-WOM (electronic word of mouth) on repurchase intention through Brand Image, with a case study of Kopi Kekinian shop consumers in Kediri City. The population in this research consists of all consumers of Kopi Kekinian shops in Kediri City. The research sample is a portion of these consumers, selected using purposive sampling, with a total of 100 respondents. The analysis results show that green marketing has a significant positive effect on Brand Image. e-WOM has a significant positive effect on the Brand Image of the product. Green marketing has not effect on repurchase intention. e-WOM has a significant positive effect on repurchase intention for the product. Brand Image has a significant positive effect on repurchase intention. Brand Image can mediate the influence of green marketing on repurchase intention for Kopi Kekinian in Kediri City. However, Brand Image does not mediate the influence of e-WOM on repurchase intention for Kopi Kekinian in Kediri City.